Effectiveness of educational programs in hearing health: a systematic review and meta-analysis. - Bramati, Luciana; Allenstein Gondim, Lys Maria; Schmidt, Lucas; Lüders, Débora; Veríssimo Meira Taveira, Karinna; Néron, Noémi; Miranda de Araujo, Cristiano; Bender Moreira de Lacerda, Adriana (International Journal of Audiology, 2024)
Objective: To evaluate the effectiveness of hearing health education programs aimed at preventing noise-induced hearing loss (NIHL), of recreational and occupational origin, by means of a systematic review and meta-analysis. Design: The search strategy was carried out in on five electronic databases, as well as referrals from experts. The risk of bias was judged, and the random effects meta-analysis was performed. The certainty of the evidence was assessed. Study sample: Effectiveness studies that used educational intervention in hearing health and prevention of NIHL were included. Results: 42 studies were included. The Dangerous Decibels program was the only one that could be quantitatively analysed and showed improvement in the post-intervention period of up to one week [SMD = 0.60; CI95% = 0.38–0.82; I2 = 92.5%) and after eight weeks [SMD = 0.45; CI95% = 0.26–0.63; I2 = 81.6%) compared to the baseline. The certainty of evidence was judged as very low. Conclusions: The Dangerous Decibels program is effective after eight weeks of intervention. The other programs cannot be quantified. They still present uncertainty about their effectiveness. The level of certainty is still low for this assessment.